Control, Capacity, and Legitimacy in Investment Treaty Arbitration. (24th September 2018) - Sharpe, Jeremy K.
Abstract : Arbitration has long been the default mechanism for resolving international investment disputes. The traditional consensus favoring arbitration, however, has now given way, and reform proposals abound. The articles by Sergio Puig and Gregory Shaffer, on institutional choice and investment law reform, and by Anthea Roberts, on incremental, systemic, and paradigmatic reform of investor-state arbitration, helpfully situate the current controversies, debates, and reform options for states. Both articles reveal just how far and fast the debate has shifted in recent years. They also confirm states' desire to exercise greater control over the regime for resolving international investment disputes. Many states continue to struggle to fully comply with their investment treaty obligations, to efficiently defend against investor claims, and to properly keep abreast of and shape developments in international investment law. Puig and Shaffer provide a useful framework for comparatively assessing possible institutional alternatives in light of their relative trade-offs. But any reform recommendations should draw lessons from states' experience with the existing regime, including states' significant problems of capacity . The merits of any reform proposals, therefore, should be measured in part by their ability to improve states' capacity to cope with the existing investment protection regime and rapidly changing developments.